Khāḍilakarāñcyā Vidyāharaṇācẽ antaraṅga - Desāī, Vasanta Śāntārāma, 1902- (SAMP early 20th-century Indian books project, 1948)
Study of Vidyāharaṇa, play by Krshṇājī Prabhākara Khāḍilakara, 1872-1948.